Combination Treatment for Severe Forms of Mucopolysaccharidosis, Type I (Hurler Syndrome): Case Report - Nato V. Vashakmadze; Natalia V. Zhurkova; Marina A. Babaykina; Albina V. Dobrotok; Olga B. Gordeeva; Leyla S. Namazova-Baranova (Вопросы современной педиатрии)
Background. Hurler syndrome (mucopolysaccharidosis, type I) is a rare hereditary disease with chronic course. The main methods for Hurler syndrome management are hematopoietic stem cell transplantation (HSCT) and enzyme replacement therapy (ERT). In recent years, combination treatment (ERT administration both before and after HSCT) has shown its efficacy in case of disease progression. Clinical case description. The presented clinical cases demonstrate the efficacy of ERT administration in patients with Hurler syndrome after HSCT: in the first clinical case due to the decrease in alpha-iduronidase activity 2 years after HSCT, in the second clinical case due to the aggravation of the patient's condition (cardiovascular and respiratory systems, hepatomegaly, although the level of enzyme and glycosaminoglycans in the patient's urine remained within normal values). Conclusion. Combination treatment including ERT not only before HSCT, but also in case of clinical state worsening after HSCT, plays significant role in stabilizing the patient's condition, preventing rapid progression of symptoms and development of life-threatening complications (especially cardiovascular ones).